2008
DOI: 10.1007/s00424-008-0564-8
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxaemia leads to major increases in inflammatory adipokine gene expression in white adipose tissue of mice

Abstract: The proposition that white adipose tissue is involved in the inflammatory response and metabolic dysregulation of endotoxaemia has been examined. Mice were injected with lipopolysaccharide (LPS; 25 mg/kg) and epididymal, perirenal and subcutaneous adipose tissue removed 4 or 24 h later. The expression of genes encoding key inflammation-related adipokines was measured by real-time polymerase chain reaction. At 24 h after the administration of LPS, there was no change in leptin mRNA level, and adiponectin mRNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…Similar to what has been reported for specific TLR agonists (16,24), we observed an inoculum dose-dependent production of IL-6 and MCP-1 (CC chemokine ligand 2), highlighting the potential role of adipocytes in the host immune response to bacterial infections. At the same time, infection with S. aureus profoundly altered the secretion of adipokines by differentiated adipocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to what has been reported for specific TLR agonists (16,24), we observed an inoculum dose-dependent production of IL-6 and MCP-1 (CC chemokine ligand 2), highlighting the potential role of adipocytes in the host immune response to bacterial infections. At the same time, infection with S. aureus profoundly altered the secretion of adipokines by differentiated adipocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, it was reported that a large dose of LPS (24 mg/kg) that resulted in a high prevalence of death (39%) in mice increased inflammatory gene expression (i.e. TNFa, IL-6, MCP-1) in WAT from surviving mice, but, notably, F4/80 and CD11b macrophage marker transcript levels did not increase 24 h after LPS injection (67). In the acute, high-dose LPS model, we observed strong activation of WAT transcript levels for a suite of proinflammatory markers, but, interestingly, some macrophage-associated markers such as CD68 and the CD11 family members were reduced, unlike in the 5-d, low-dose LPS studies.…”
Section: Discussionmentioning
confidence: 98%
“…Although acute inflammation in vitro has well-described negative effects on adiponectin biosynthesis in cultured adipocytes, 14 the effects of acute inflammation in vivo are unclear; in mice, lipopolysaccharide injection lowers ADIPOQ gene expression from white AT, 30 but in patients with diabetes mellitus, short-term infusion of IL-6 increases ADIPOQ gene expression in subcutaneous AT. 31 We induced systemic low-grade inflammation in healthy individuals by using S. typhi vaccine, 23 and we observed that this type of inducible inflammation decreased circulating adiponectin levels within 24 hours compared with placebo, having no effects on circulating BNP.…”
Section: Discussionmentioning
confidence: 99%